How the Internet Shapes Collective Actions - Schumann, S. author. aut Link
VIII, 74 p.
Keywords: After a Facebook rebellion in Egypt and Twitter protests in Turkey, the internet has been proclaimed as a globe-shifting, revolutionizing force that can incite complex social phenomena such as collective actions. This book critically assesses this claim and highlights how internet use can shape mobilizing processes to foster collective actions.